Robust control of power converter via uncertainty and disturbance estimator - Li, Ziqi (Nanyang Technological University, 2021)
The uncertainty and disturbance estimator (UDE)-based robust control method has been extensively studied and employed in many uncertain systems to realize disturbance rejection and address the instability issues. Among those uncertain systems, inverters play an important part in energy conversion applications. Existing works in the literature mainly focus on reducing the total harmonic distortion (THD) of inverter’s output voltage under nonlinear loads, which could enhance the quality of the inverter’s output voltage. However, such works cannot assure the robustness in the presence of fundamental frequency fluctuations. In this thesis, based on the UDE-based robust control structure, dual-loop control framework is employed to decouple the reference tracking and disturbance rejection of the inverter in the frequency domain. A multi-band-stop filter is designed to minimize the total harmonic distortion (THD) of inverter’s output voltage by modifying the magnitude of output impedance only around the harmonic frequencies directly. In addition, increasing the bandwidth of each band-stop filter could guarantee the robust performance to fundamental frequency fluctuations, thus enhancing the quality of inverter’s output voltage as well. Besides, the design with multi-time-delayed filter to further reduce output voltage THD was introduced, including the principle and overall control framework. Finally, the performance of the proposed control design is verified with the experimental results. Also, the experiment compared with UDE-based controller equipped with single-time-delayed filter and multi-time-delayed filter has been conducted.